POLA PEMANFAATAN PELAYANAN KESEHATAN DAERAH TERTINGGAL, PERBATASAN, KEPULAUAN, DAN TERPENCIL (DTPK-T) DI INDONESIA (ANALISIS DATA RISKESDAS 2013) - Sri Wiyanti; Hari Kusnanto; Mubasysyir Hasanbasri (Journal of Health Service Management, 2016)
Background: Utilization of health services is an importantelement in determining the health status of the community.Information on the utilization of health services are needed byhealth services management, in taking appropriate policy(Feldstein 1988). communities disadvantaged areas, islands,and remote border (DTPK-T) have limitations in the use ofhealth services, this is due to geographical conditions that aredifficult to reach, limited infrastructure and health humanresources that add to the complexity of the problem.Objectives: Reviewing and analyzing the patterns of utilizationof health services for people in underdeveloped regions, border,island, and remote. Method: This study uses secondary data from the Basic HealthResearch (RISKESDAS) in 2013, with a cross-sectional design.In this study focused to see the pattern of utilization of the publicin disadvantaged areas, border, island, and remote in obtaininghealth services at the health center. Results: Least developed society, border, island, and remoteuse more health centers, out of total 42.623 respondents,approximately 18.882 people or 43.5% are utilizing the serviceshealth centers, physician practices 19.5%, gender, economicstatus, education, travel time and transportation costs, doctor'sdiagnosis of the disease in the suffering of both communicableand non-communicable, rural location had a significant effect onhealth care utilization, while the category of regions did not havea significant effect on the utilization of health centers.Conclusion: People in, Less developed, border, island, andremote areas (DTPK-T) have made use of basic health carefacilities (health centers), in addressing health issues. Specialpolicies are needed in order to improve the quality of care byproviding health resources, infrastructure, and availability ofdrugs.